Identification of Benzyloxy Carbonimidoyl Dicyanide Derivatives as Novel Type III Secretion System Inhibitors via High-Throughput Screening - Ma, Yi-Nan; Chen, Liang; Si, Nai-Guo; Jiang, Wen-Jun; Zhou, Zhi-Gang; Liu, Jun-Li; Zhang, Li-Qun (Frontiers in Plant Science, 2019)
The type III secretion system (T3SS) in many Gram-negative bacterial pathogens is regarded as the most critical virulence determinant and an attractive target for novel anti-virulence drugs. In this study, we constructed a T3SS secretion reporter containing the β-lactamase gene fused with a signal peptide sequence of the T3SS effector gene, and established a high-throughput screening system for T3SS inhibitors in the plant pathogenic bacterium Acidovorax citrulli. From a library of 12,000 chemical compounds, we identified a series of benzyloxy carbonimidoyl dicyanide (BCD) derivatives that effectively blocked T3SS-dependent β-lactamase secretion. Substitution of halogens or nitro groups at the para-position on the benzene ring contributed to an increased inhibitory activity. One representative compound, BCD03 (3,4-dichloro-benzyloxy carbonimidoyl dicyanide), dramatically reduced pathogenicity of A. citrulli on melon seedlings, and attenuated hypersensitive responses in the non-host Nicotiana tabacum caused by pathogenic bacteria A. citrulli, Xanthomonas oryzae pv. oryzae and Pseudomonas syringae pv. tomato at sub-MIC concentrations. Western blotting assay further confirmed that BCD03 inhibited effector secretion from the above bacteria via T3SS in the liquid medium. Taken together, our data suggest that BCD derivatives act as novel inhibitors of T3SS in multiple plant bacterial pathogens.